2013
DOI: 10.1249/mss.0b013e3182831db1
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Fitness, Body Mass Index, and Risk of Depression among Adolescents

Abstract: These findings indicate that a healthy level of cardiorespiratory fitness was associated with a lower level of depression as measured by the CES-DC. Because of the cross-sectional nature of this study, no cause and effect relations can be assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 24 publications
7
27
0
2
Order By: Relevance
“…More recently, the fitness-depression relationship has been examined among adolescents and, consistent with the adult findings, CRF is related to lower levels of depressive symptomatology in both cross-sectional Ortega et al, 2008;Shomaker et al, 2012;Rieck et al, 2013;Tomson, Pangrazi, Friedman, & Hutchison, 2003), as well as, longitudinal studies (Crews et al, 2004;Dunton et al, 2007;Kelly et al, 2011;Voorhees et al, 2008). For example, Greenleaf et al (2010) found that after controlling for Social Economic Status (SES) female adolescents whose fitness scores fell in the Healthy Fitness Zone [HFZ], based on a standardized CRF test, had significantly lower scores on a measure of depressed mood compared to the female adolescents whose fitness scores fell in the Needs Improvement Zone [NIZ] (r = 0.54; R 2 = .29); no significant relation existed between fitness and depression for the male adolescents.…”
Section: Physical Activity and The Fitness-depression Relationmentioning
confidence: 73%
See 2 more Smart Citations
“…More recently, the fitness-depression relationship has been examined among adolescents and, consistent with the adult findings, CRF is related to lower levels of depressive symptomatology in both cross-sectional Ortega et al, 2008;Shomaker et al, 2012;Rieck et al, 2013;Tomson, Pangrazi, Friedman, & Hutchison, 2003), as well as, longitudinal studies (Crews et al, 2004;Dunton et al, 2007;Kelly et al, 2011;Voorhees et al, 2008). For example, Greenleaf et al (2010) found that after controlling for Social Economic Status (SES) female adolescents whose fitness scores fell in the Healthy Fitness Zone [HFZ], based on a standardized CRF test, had significantly lower scores on a measure of depressed mood compared to the female adolescents whose fitness scores fell in the Needs Improvement Zone [NIZ] (r = 0.54; R 2 = .29); no significant relation existed between fitness and depression for the male adolescents.…”
Section: Physical Activity and The Fitness-depression Relationmentioning
confidence: 73%
“…Such declines in physical activity and fitness are associated with increased risk of major health issues, including significant weight gain (Fogelholm & Kukkonen-Harjula, 2000;LahtiKoski, Pietinen, Heliovaara, & Vartianinen, 2002;Rieck, Jackson, Martin, Petrie, & Greenleaf, 2013;Schmitz, Jacobs, Leon, Schreiner, & Sternfeld, 2000). In contrast, increases in physical activity (Biddle & Asare, 2011;Boone & Leadbetter, 2006;Dunton, Atienza, Tscherne, & Rodriguez, 2011;Kelly et al, 2011;Motl, Birnbaum, Kubik, & Dishman, 2004) and improvements in CRF (Dunton et al, 2007;Ortega et al, 2008) are associated with psychological and physical health, and more specifically reduction in depression scores among adolescents.…”
Section: Physical Activity and The Fitness-depression Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…Com exceção do voleibol, são esportes que demandam intensidade moderada a vigorosa e são de longa duração, fato que beneficia a saúde de adolescentes como, por exemplo, resultando em aumento da aptidão cardiorrespiratória 24 . As informações disponíveis da literatura, somados com os encontrados no presente estudo, indicam a necessidade da prática de atividade física moderada à vigorosa e da prática esportiva com objetivo de prevenir os agravos à saúde relacionados à baixa aptidão cardiorrespiratória 1,2 .…”
Section: Discussionunclassified
“…A condição socioeconômica foi estimada por meio dos Critérios de Classificação Econômica do Brasil 14 O estado nutricional foi estimado por meio do Índice de Massa Corporal, calculado por meio da equação massa corporal (kg)/estatura(m) 2 . A estatura foi medida por meio de uma fita métrica fixada na parede (Sanny, São Paulo, Brasil), com precisão de 1 mm e a massa corporal total por meio de uma balança eletrônica com precisão de 100 g e capacidade de 150 kg (Plenna, modelo MEA-03140, São Paulo, Brasil), de acordo com procedimentos já descritos 18 .…”
Section: Métodosunclassified